The past century of coral bleaching in the Saudi Arabian central Red Sea - DeCarlo, Thomas M. (PeerJ, 2020)
Accurate knowledge of the spatial and temporal patterns of coral bleaching is essential both for understanding how coral reef ecosystems are changing today and forecasting their future states. Yet, in many regions of the world, the history of bleaching is poorly known, especially prior to the late 20th century. Here, I use the information preserved within skeleton cores of long-lived Porites corals to reconstruct the past century of bleaching events in the Saudi Arabian central Red Sea. In these cores, skeletal “stress bands”—indicative of past bleaching—captured known bleaching events that occurred in 1998 and 2010, but also revealed evidence of previously unknown bleaching events in 1931, 1978, and 1982. However, these earlier events affected a significantly lesser proportion of corals than 1998 and 2010. Therefore, coral bleaching may have occurred in the central Red Sea earlier than previously recognized, but the frequency and severity of bleaching events since 1998 on nearshore reefs is unprecedented over the past century. Conversely, corals living on mid- to outer-shelf reefs have not been equally susceptible to bleaching as their nearshore counterparts, which was evident in that stress bands were five times more prevalent nearshore. Whether this pattern of susceptible nearshore reefs and resistant outer-shelf reefs continues in the future remains a key question in forecasting coral reef futures in this region.